Management of Splenic Injury at B&C Medical College, Teaching Hospital and Research Centre - Baskota, Bashu Dev; Pun, Deepak; Payangu, Bimas; Bhagat, Sachin (Medical Journal of Eastern Nepal, 2023)
Background: In all blunt abdominal injuries splenic injury relates to about 40%. Splenectomy is the preferred treatment choice for blunt splenic injury in hemodynamically unstable patients. The low-grade splenic injuries and stable patients are mostly treated by non-operative management (NOM) at today era. Consensuses have not been yet formulated about the management of high-grade splenic injuries in hemodynamically stable patients. So, this study analyzes the treatment of patients with high-grade splenic injuries in our institution. Methods: This study includes all the patients with splenic injuries presented to our hospital during the 5 years period from 2017 to 2022. The datas regarding primary baseline at emergency, complications and mortality were collected from the patient records at medical record section. Based on splenic injury and the treatment they received, they were grouped accordingly. Results: In a total of 38 cases of spleen injuries, the most common mode of injury was a road traffic accident (RTA) 84% followed by fall injury (10%) spontaneous rupture of the spleen and blast injury 3% each. Sixty-six per cent of the cases underwent operative management out of which 96% cases had a splenectomy and 4% cases had a splenic repair. There was 5% mortality and 95% recovery without residual morbidity. Conclusion: Most of the cases with spleen injury were managed with a favorable outcome. The careful patient selection for non-operative management will result in higher splenic salvage with close monitoring in an intensive care unit.